Interpreting the Right to Strike through ILO’s Advisory Opinion Initiative - Adhijoso, Putri Ayu Musthikaweni (Center for Law and Responsible Business Studies, 2026)
This paper explores the emerging recognition of the right to strike within international law and its interpretation under the International Labour Organization (ILO) framework. The research focuses on whether the right to strike, as linked to freedom of association in ILO Convention No. 87, has developed into customary international law. Using a normative juridical method as its principal approach and supported by statutory and comparative approaches, the study analyses relevant legal instruments such as the Universal Declaration of Human Rights, the International Covenant on Economic, Social and Cultural Rights, and the ILO Constitution. It also examines the ongoing debate among ILO constituents and the possibility of seeking an advisory opinion from the International Court of Justice (ICJ) to clarify this issue. Through a comparative analysis of the Netherlands, France, Germany, and Indonesia, the paper finds that while most legal systems acknowledge the right to strike as part of freedom of association, its implementation differs depending on each country’s constitutional design and industrial relations culture. The findings suggest that the right to strike has indeed attained the status of customary international law through widespread state practice and opinio juris, although its practical enforcement continues to depend on domestic legal and procedural frameworks.